Use Of Foreign Experience Of Insurance Through The Organization Of Risk Mutual Insurance Companies In Agricultural Enterprises (Eurasian Journal of History, Geography and Economics, 2024)
In the article, the risks associated with the activities of agricultural enterprises and the specific features and advantages of insurance through the establishment of mutual insurance societies and a long history in this regard are discussed. Canada's experience is highlighted as the experience of foreign countries, and recommendations for applying this experience in Uzbekistan are developed.